2016
DOI: 10.1016/j.conbuildmat.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on effect of aggregate on three non-destructive testing properties of concrete subjected to sulfuric acid attack

Abstract: In order to investigate the effect of aggregates on the concrete sulfuric acid resistance, accelerated corrosion experiments were conducted with four types of concretes composed of coarse and fine aggregates with two different chemical compositions. All the concretes with the same water/cement ratio of 0.45, and the pH value was kept in the range of 0.93 to 0.97. With continuous monitoring of each concrete specimen, corrosion depth, mass loss, and dynamic modulus elasticity loss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A few studies have been conducted to measure the degradation depths of OPC-based binder or AAMs after immersion in various acidic solutions and related degradation mechanisms were also proposed [3,46,53,[56][57][58][59]. The experiment work of Lloyd et al [46] revealed that the degradation depth is a more reliable method to assess the degradation kinetics, particularly for AAMs compared to mass loss.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been conducted to measure the degradation depths of OPC-based binder or AAMs after immersion in various acidic solutions and related degradation mechanisms were also proposed [3,46,53,[56][57][58][59]. The experiment work of Lloyd et al [46] revealed that the degradation depth is a more reliable method to assess the degradation kinetics, particularly for AAMs compared to mass loss.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, concrete structures in industrial zones are susceptible to deterioration due to acid rain, of which sulfuric acid is a chief component. Portland cement concrete hydration items are alkaline and have a pH rating of 12 to 13.5 [ 39 ]. For sulphate attacks on concrete (sodium sulphate), there are two types, namely external and internal.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced concrete structures have been the most widely used structures in civil engineering since the late 19th century due to good mechanical properties, low cost, and good durability in normal environments [1][2][3][4]. However, under corrosive environmental conditions (such as marine environment, deicing salt environment, carbonation environment, acid corrosion environment, etc.…”
Section: Introductionmentioning
confidence: 99%